2015
DOI: 10.15403/jgld.2014.1121.cpa
|View full text |Cite
|
Sign up to set email alerts
|

Primary Biliary Cirrhosis – Autoimmune Hepatitis Overlap Syndrome Associated with Dermatomyositis, Autoimmune Thyroiditis and Antiphospholipid Syndrome

Abstract: Autoimmune liver diseases may be associated with extrahepatic autoimmune pathology. We report the case of a 52-year old woman who initially presented to the gastroenterology department for extreme fatigue, pale stools, dark urine and pruritus. Laboratory tests showed significant cholestasis and elevation of aminotransferase levels. Immunological tests revealed positive antinuclear (ANA=1:320) and antimitochondrial antibodies (AMA=1:40) with negative anti-smooth muscle and liver kidney microsomal type 1 antibod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 17 publications
(19 reference statements)
0
9
0
1
Order By: Relevance
“…AMA-associated myositis is not a well-recognized clinical entity. However, there is a growing literature supporting such an association, with at least 24 case reports to date found in English [1532]. A majority of these cases emerge from East Asia, and a recent comprehensive study from Japan comprising 212 patients with myositis reported a prevalence of 11.3% of AMA-associated myositis in their cohort[33].…”
Section: Discussionmentioning
confidence: 99%
“…AMA-associated myositis is not a well-recognized clinical entity. However, there is a growing literature supporting such an association, with at least 24 case reports to date found in English [1532]. A majority of these cases emerge from East Asia, and a recent comprehensive study from Japan comprising 212 patients with myositis reported a prevalence of 11.3% of AMA-associated myositis in their cohort[33].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we found that the clinical features in patients with AMAs showed great variability. Firstly, although AMAs only occurred in adult IIM patients, the age at onset ranged from 23 years to 86 years and the mean age at onset ranged from the fourth decade to the seventh decade [3][4][5]7,8,[20][21][22][23][24][25][26] . Besides, the average disease duration varied from 10 months (in our study) to 6.5 years, and the prevalence of chronic disease duration varied from approximately 30% (in our study) to 85% [3,5,6] .…”
Section: Discussionmentioning
confidence: 99%
“…Watt et al [ 1 ] reported that 84 of 160 (53%) PBC patients had at least one additional extrahepatic autoimmune condition, and 16 of 37 (43%) patients developed thyroid diseases prior to the detection of PBC, while 19 of 37 (51%) patients detected thyroid diseases at the same time or following the diagnosis of PBC; 10 of 12 (83%) patients developed sclerosis symptoms prior to the detection of PBC. Another report also showed that the onset time of AIH and dermatomyositis (DM) was uneven [ 2 ]. While explanations for the discrepancies in incidence and onset time are lacking, different geographical and genetic backgrounds in studies may be involved.…”
Section: The Spectrum Of Ehiads In Patients With Aildsmentioning
confidence: 99%